2010
DOI: 10.1152/ajprenal.00542.2009
|View full text |Cite
|
Sign up to set email alerts
|

Postobstructive regeneration of kidney is derailed when surge in renal stem cells during course of unilateral ureteral obstruction is halted

Abstract: Goligorsky MS. Postobstructive regeneration of kidney is derailed when surge in renal stem cells during course of unilateral ureteral obstruction is halted. Am J Physiol Renal Physiol 298: F357-F364, 2010. First published November 11, 2009 doi:10.1152/ajprenal.00542.2009.-Unilateral ureteral obstruction (UUO), a model of tubulointerstitial scarring (TIS), has a propensity toward regeneration of renal parenchyma after release of obstruction (RUUO). No information exists on the contribution of stem cells to this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…Irreversible UUO allows the study of inflammation and tissue injury including the role of various leukocytes and mediators [1][2][3]10 whilst study of the R-UUO model enables researchers to explore the resolution of renal injury and associated tissue remodeling. 6,7,[11][12][13][14][15] Other investigators have used different methods to induce and reverse ureteric obstruction. In the first description of the R-UUO model, the left ureter of male C57BL/6 mice was obstructed with an atraumatic microvascular clamp via a flank incision.…”
Section: Discussionmentioning
confidence: 99%
“…Irreversible UUO allows the study of inflammation and tissue injury including the role of various leukocytes and mediators [1][2][3]10 whilst study of the R-UUO model enables researchers to explore the resolution of renal injury and associated tissue remodeling. 6,7,[11][12][13][14][15] Other investigators have used different methods to induce and reverse ureteric obstruction. In the first description of the R-UUO model, the left ureter of male C57BL/6 mice was obstructed with an atraumatic microvascular clamp via a flank incision.…”
Section: Discussionmentioning
confidence: 99%
“…Although their origin is uncertain, myofibroblasts are probably derived (1) from resident interstitial fibroblasts (e.g., Picard et al 2008), (2) by Snai1- or Id1-dependent transcriptional reprogramming of renal pericytes or perivascular fibroblasts (Humphreys et al 2010; Cook 2010; Roufosse et al 2006; Lin et al 2008), (3) as a consequence of tubular epithelial-to-mesenchymal transdifferentiation (EMT; Yamashita et al 2005; Kalluri and Neilson 2003; Iwano et al 2002; Eddy 2009; Iwano and Neilson 2004; Liu 2006, 2010; Grande and Lopez-Novoa 2009), or (4) by extra-renal recruitment from the circulation or bone marrow (Ricardo et al 2008). Indeed, the mobilization of stem-like cells accompanies post-obstructive kidney regeneration suggesting that renal capsule-derived, hematopoietic, or mesenchymal progenitor cells participate in repair (Park et al 2010aPark et al 2010b; Yamashita et al 2005). Whether progenitor involvement has a positive or negative effect on outcome, however, is controversial, although renal-artery-delivered human mesenchymal stem cells appear to attenuate UUO-induced fibrosis (Asanuma et al 2010).…”
Section: Cellular Events In Obstructive Renal Diseasementioning
confidence: 99%
“…The therapeutic delivery of stem cells has been demonstrated to enhance the repair and regeneration of the kidney after injury [1][2][3][4][5][6][7]. Although various multipotent stem cells have been examined for their repair potential, endothelial progenitor cells (EPCs) have demonstrated remarkable renoprotective potential.…”
Section: Introductionmentioning
confidence: 99%
“…However, during kidney and vascular injury, the competence of endogenous EPCs is often compromised, leading to accelerated progression of the injury [7]. Previous studies from our laboratory and others have shown that delivered EPCs counter the vascular impairment that occurs during the course of acute kidney injury (AKI) [1,6,7,11] and improve renal function, attenuate inflammation, decrease tubular and vascular damage, and enhance angiogenesis [1,4,6,7].…”
Section: Introductionmentioning
confidence: 99%